Exploring Off-site Construction and Building Information Modelling Integration Challenges; Enhancing Capabilities within New Zealand Construction Sector - Ghalenoei, Nazanin Kordestani; Jelodar, Mostafa Babaeian; Paes, Daniel; Sutrisna, Monty (IOP conference series. Earth and environmental science, 2022)
Over the last few years off-site construction (OSC); which is essentially manufacturing different components in a controlled environment, has become popular in the construction industry. This method has the advantages of simplicity, speed, reducing project duration, and minimising construction waste. Therefore, a growing body of literature recognises the importance of OSC to gain better project performance. While OSC has received considerable critical attention, to enhance OSC applications, integrating advanced technologies such as building information modelling (BIM) is essential. There is a lack of research addressing the integration of BIM and OSC, particularly in New Zealand, and few studies investigated the current subject. Therefore, this study focuses on finding the existing OSC and BIM integration challenges within the New Zealand construction sector. The objective of this study has been investigated through literature review and interviews with experts. The common challenges of OSC and BIM integration were identified and classified. Human resources, documentation, managerial, and organisational are the main challenges. This paper is dedicated to exploring OSC and BIM integration in New Zealand, an essential step for the OSC application strategies within the construction sector. This study findings will lend to the construction sector expanding capabilities to improve the status quo and optimise OSC applications through advanced technologies.